Estudos em hospitalidade e perfil dos pesquisadores-doutores brasileiros - MARCELINO, Grace Kelly (2016)
Who are the Brazilian researchers-doctors studying hospitality? How do they treat this main theme in their works? This documentary research study aims to investigate the production of hospitality in Brazil and to identify the profile of its researchers-doctors. The study material was obtained by the Lattes Platform curricula. The analysis of scientific journals has been made using the methodology of state of knowledge and content analysis, based on three categories - common sense, sociocultural and business. The results showed that methodology applied on hospitality studies interferes in the analysis results; that in both methods applied, the socio-cultural category is the one that contains more articles; that the authors most widely used by researchers-doctors are Levinas, Derrida and Camargo; these researchers-doctors come from these following areas: Tourism, Business Administration, Engineering, Communication and Education and the majority work in public institutions of higher education.